2016
DOI: 10.1021/acs.accounts.6b00268
|View full text |Cite
|
Sign up to set email alerts
|

Fine Design of Photoredox Systems for Catalytic Fluoromethylation of Carbon–Carbon Multiple Bonds

Abstract: Trifluoromethyl (CF3) and difluoromethyl (CF2H) groups are versatile structural motifs, especially in the fields of pharmaceuticals and agrochemicals. Thus, the development of new protocols for tri- and difluoromethylation of various skeletons has become a vital subject to be studied in the field of synthetic organic chemistry. For the past decades, a variety of fluoromethylating reagents have been developed. In particular, bench-stable and easy-to-use electrophilic fluoromethylating reagents such as the Umemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
156
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 504 publications
(158 citation statements)
references
References 81 publications
0
156
0
2
Order By: Relevance
“…Further experiments revealed that the photocatalyst was essential for the success of this reaction, no isomerization product could be detected in the absence of catalyst (entry 2). Encouraged by the initial results, we examined several catalysts, sensitizers for this photo-catalytic transformation and we found that transition-metal photoredox catalysts would generally catalyze this reaction, but produced diverse Z/E selectivity, iridium catalyst performed better than its ruthenium counterpart (entries 3 and 4), with fac-Ir(ppy) 3 as the catalyst of choice to give the best selectivity. The varied catalytic activities could directly relate to the different emissive energies of the catalysts used in the investigation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further experiments revealed that the photocatalyst was essential for the success of this reaction, no isomerization product could be detected in the absence of catalyst (entry 2). Encouraged by the initial results, we examined several catalysts, sensitizers for this photo-catalytic transformation and we found that transition-metal photoredox catalysts would generally catalyze this reaction, but produced diverse Z/E selectivity, iridium catalyst performed better than its ruthenium counterpart (entries 3 and 4), with fac-Ir(ppy) 3 as the catalyst of choice to give the best selectivity. The varied catalytic activities could directly relate to the different emissive energies of the catalysts used in the investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The varied catalytic activities could directly relate to the different emissive energies of the catalysts used in the investigation. fac-Ir(ppy) 3 catalyst, which has a greater emissive energy (494 nm, 57.8 kcal mol −1 ) than the Ru(bpy) 3 Cl 2 catalyst (615 nm, 46.5 kcal mol −1 ) [8,23], supposedly efficiently promotes the energy transfer to the substrate, its longer excited-state lifetime could also facilitate this process [24]. It is worth noting that (−)-riboflavin only showed marginal effect on the isomerization under visible light condition, compared with its significant performance under UV light (entry 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations